Nanoengineered polyelectrolyte micro- and nano-capsules as fluorescent potassium ion sensors. - Brown, J.Q (IEEE Engineering in medicine and biology magazine)
Hollow polyelectrolyte capsules have been fabricated and initial experiments have shown their functionality as biosensors, with potassium ions as a sample analyte. Sensors such as these could be employed in basic research, such as in monitoring cells in culture, as well as diagnostic tools in medicine. The sensors can monitor real-time potassium ion transients with high sensitivity due to the packaging of many probe molecules in a small volume. Further work on addition of coatings with biocompatible properties or selective binding molecules (e.g. antibodies) may enable employment of these systems in a broader range of applications.